MARINE EUTROPHICATION - Karydis, Michael; Kitsiou, Dimitra ([Place of publication not identified], CRC Press, 2019)
Marine eutrophication has been recognized as a global problem with adverse effects on ecosystem's health and the economies of coastal states. Most conventions regarding marine environmental protection of Regional Seas have given priority to eutrophication and relevant management practices. This book presents a global perspective of eutrophication in most of the Regional Seas, including the legal framework, assessment and management practices. Information on ecosystem's impact as well as an outline of the methods used for assessing eutrophication is also provided. This volume will be useful to research students, marine scientists and policy makers working in marine environmental management. Key Features: Contributes to the understanding of the eutrophication processes and problems Presents an extensive account of the data analysis methods used for the quantitative assessment of eutrophication Looks the eutrophication status of the main regional seas Provides information on eutrophication politics and measures to mitigate eutrophication
OCLC-licensed vendor bibliographic record.
Keywords: NATURE / Ecology; SCIENCE / Life Sciences / Biology / Marine Biology; SCIENCE / Life Sciences / General; Marine eutrophication; Marine ecology